Introduction to cost-benefit analysis : looking for reasonable shortcuts - Rus, Gines de (Edward Elgar, 2010)
This accessible and non-technical introductory text presents the principal methods and key concepts involved in understanding and applying cost-benefit analysis, and demonstrating how to evaluate whether an investment project or policy proposal will contribute to increase social welfare. Gines de Rus incorporates the latest thinking on issues such as the treatment of risk and uncertainty, and the importance of institutional arrangements in ensuring the correct use of the technique